2014
DOI: 10.18632/oncotarget.2139
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor-like protein is required for prostate tumor growth in the TRAMP mouse model

Abstract: The Ron receptor is deregulated in a variety of cancers. Hepatocyte growth factor-like protein (HGFL) is the ligand for Ron and is constitutively secreted from hepatocytes into the circulation. While a few recent reports have emerged analyzing ectopic HGFL overexpression in cancer cells, no studies have examined the effect of host-produced HGFL in tumorigenesis. To examine HGFL function in prostate cancer, the TRAMP mouse model, which is predisposed to develop prostate tumors, was utilized. Prostate tumors fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…Importantly, this is the first study to describe the tumor cell autonomous production of HGFL from mammary tumors cells. Recent publications from our group have shown that HGFL expression is present in the developing mammary gland as well as in prostate tumor cells [ 39 , 50 ]. In this study, we demonstrate heightened HGFL mRNA expression during tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this is the first study to describe the tumor cell autonomous production of HGFL from mammary tumors cells. Recent publications from our group have shown that HGFL expression is present in the developing mammary gland as well as in prostate tumor cells [ 39 , 50 ]. In this study, we demonstrate heightened HGFL mRNA expression during tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…RON receptor signaling has been established as a central factor in promoting prostate cancer in several murine models [6] , [12] , [13] , [16] , [17] . To assess the significance of RON expression in human prostate cancer, multiple human data sets were analyzed using the Cancer Outlier Profile Analysis (COPA) method [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] .…”
Section: Resultsmentioning
confidence: 99%
“…RON is a cell surface RTK that is primarily expressed on epithelial cells and select macrophage populations, where activation of RON will function to reduce inflammation and promote wound healing [6] , [7] , [8] , [9] , [10] , [11] . Overexpression of RON has been observed in a number of solid cancers, and within cancer, RON promotes phenotypes such as survival, proliferation, migration/invasion, angiogenesis, and stemness [12] , [13] , [14] , [15] . Specifically, in prostate cancer, previous studies have established the RON receptor as critical for cancer development and progression [6] , [12] , [16] , [17] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations